Predictors of hospital-acquired adverse drug reactions: a cohort of Ugandan older adults - Tadele Mekuriya Yadesa (BMC Geriatrics, 2022)
Abstract Background Globally, it is estimated that the number of older adults will become 2 billion by 2050. The identification of the predictors of adverse drug reaction (ADR) in hospitalized older patients is crucial to the development of prediction tools and preventive strategies to mitigate the burden of ADRs. This study aimed to determine the predictors of hospital-acquired ADR occurrence among hospitalized older adults in a low-income country. Methods We conducted a prospective cohort of older adults admitted to medical, oncology, and surgery wards at Mbarara Regional Referral Hospital (MRRH) for a consecutive 6 months where each patient was followed up daily from admission to discharge. We used Edwards and Aronson’s definition of ADR and the Naranjo ADR Causality Scale. We employed Beer’s criteria and Lexicomp to determine potentially inappropriate medications, and drug interactions, respectively. We conducted univariate and multivariable logistic regression using Statistical Package for the Social Science (SPSS) Version 23.0. Results Out of 523 participants with median (Inter Quartile Range) age of 67 (62–76) years, 256 (48.9%) experienced at least one ADR. Independent predictors of occurrence of hospital acquired ADRs included age of 60–75 (Adjusted odds ratio (AOR) = 1.97, 95% C.I: 1.14–3.41; p value = 0.015) compared to > 75 years, previous ADR in 1 year (AOR = 2.43, 95% C.I: 1.42–4.17; p value = 0.001), potentially inappropriate medication (AOR = 4.56, 95% C.I: 2.70–7.70; p value< 0.001), polypharmacy (AOR = 3.29, 95% C.I: 1.98–5.46; p value< 0.001)), having a Charlison Comorbidity Index (CCI) ≥ 6 (AOR = 8.47, 95% C.I: 4.85–14.99; p value< 0.001), having heart failure (AOR = 2.83, 95% C.I: 1.34–6.02; p value = 0.007) or kidney disease (AOR = 1.95, 95% C.I: 1.05–3.61; p value = 0.034) and a hospital stay > 10 days (AOR = 3.53, 95% C.I: 1.89–6.61; p value< 0.001) compared to < 5 days. Conclusion The current prevalence of ADR is higher than previously reported in high-income countries. Disease-related factors followed by medication-related factors were shown to be the most important predictors of hospital-acquired ADRs. CCI and PIM showed the strongest association with ADR. The predictors of ADRs identified in our study were generally comparable with those reported by previous studies. Plain language title Conditions that predispose older patients to experience harmful effects from their medications while in hospital. Plain language summary Identifying the conditions that predispose older adults to incur harmful effects of their medications helps to plan on how best to predict, take precautions and closely follow up on them and thus, to prevent these undesirable outcomes. This study aimed to identify these conditions which determine which older adults are higher risk to incur these harmful undesirable effects of medicines. Everydayduring their hospital stay, we closely followed older patients who were 60 years and above from their entry to the hospital wards until they left the hospital. We interviewed the participants, reviewed their medication files and we also examined them physically to identify any unwanted and harmful outcome from their current medications. Out of 523 participants, almost half of them experienced at least one harmful or undesired effect related to their medicine. Conditions which predisposed them to experience a harmful effect from their medicines included being in age bracket of 60–75 years, having a history of experiencing harmful outcomes from medicines in the previous 1 year, taking a medication which was listed as potentially inappropriate for older adults, taking 5 or more medications concurrently, having a lower 10 years survival chance, having heart or kidney disease and a hospital stay > 10 days.